2017
DOI: 10.1016/j.ydbio.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell cysts and simultaneous sperm and oocyte production in a hermaphroditic nematode

Abstract: Studies of gamete development in the self-fertile hermaphrodites of Caenorhabditis elegans have significantly contributed to our understanding of fundamental developmental mechanisms. However, evolutionary transitions from outcrossing males and females to self-fertile hermaphrodites have convergently evolved within multiple nematode sub-lineages, and whether the C. elegans pattern of self-fertile hermaphroditism and gamete development is representative remains largely unexplored. Here we describe a pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Previously, we showed that sperm production in A. rhodensis hermaphrodites differs from that in C. elegans , because A. rhodensis hermaphrodites produce sperm from discrete clusters of spermatogonial cells—both simultaneously and continuously along with oocytes [ 15 ]. In addition, A. rhodensis hermaphrodites, like A. rhodensis males, produce only two rather than four functional sperm during meiosis [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we showed that sperm production in A. rhodensis hermaphrodites differs from that in C. elegans , because A. rhodensis hermaphrodites produce sperm from discrete clusters of spermatogonial cells—both simultaneously and continuously along with oocytes [ 15 ]. In addition, A. rhodensis hermaphrodites, like A. rhodensis males, produce only two rather than four functional sperm during meiosis [ 6 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…During anaphase II, the lagging X chromatid invariably ends up in the functional male sperm, whereas the other chromosomal complement is discarded in a “residual body” ( Figure 2 ) [ 6 , 7 ]. In XX A. rhodensis hermaphrodites, clusters of synchronously dividing spermatocytes arise from discrete clusters of spermatogonial cells [ 15 ]. Analysis of 520 hermaphrodite gonads yielded 16 clusters with anaphase II stage spermatocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, A. rhodensis males produce haploid cells that are discarded as female polar bodies 11,12 , and sex determination is influenced by the mother’s age 13 . A. rhodensis is unique among hermaphroditic nematodes in that two distinct groups of stem cells in the hermaphrodite germline produce either sperm or oocytes 14 . Thus, Auanema is a suitable model for basic cell biology, genetics, and evolution.…”
Section: Introductionmentioning
confidence: 99%